(untitled) (International journal of artificial intelligence, 2026)
This article discusses the theoretical foundations and practical significance of developing construction and modeling competencies in future primary school teachers. In particular, it analyzes the essence of the concepts of construction and modeling, their role in the educational process, and their importance in teachers’ professional activities. Furthermore, modern pedagogical methods, innovative approaches, and new technologies that contribute to the formation of these competencies are examined. The article also provides recommendations for solving problems that may arise in the educational process.